FACEBOOK AS A DAKWAH COMMUNICATION MEDIA PESANTREN KIAI SYARIFUDDIN in FIGHTING RADICALISM - M Zakaria Husni (Indonesian Journal of Islamic Communication, 2023)
Abstrak: Pesantren as the pioneer of Pancasila in stemming radicalism and accusations towards the state which have been irrelevant in implementing Pancasila. There are many hoax news that are spreaded in social media today for deceiving and undermining the country massively. The media is misused in indoctrinating digital society thougt today, by using social media freely, it is very easy to doctrin a society that was originally calm and peaceful to make a hard and challenging society that seems to be incompatible with the diversity and context of Islam. The formulation of the problem in the research is to analyze the use of social media (Facebook) as a means of dakwah at Pesantren Kiai Syarifuddin, further, the values of Islamic dakwah through social media (Facebook) at Pesantren Kiai Syarifuddin? This study used a constructivist approach. In this research, the researcher reveals and analyzes the reality of dakwah social at Pesantren which is a construction. The results of this research were: social media at Pesantren Kiai is active in spreading the values of dakwah. It can be seen on how the social media at Pesantren Kiai Syarifuddin spreads all activities that seek to raise awareness of the importance of dakwah through social media. All the activities which were conducted by Pesantren was posted in its social media, starting from reciting classical book, podcasts speeches and so on.